Bridging the gap: how education transforms health outcomes and influences health inequality in rural China - Chen, Jingyuan; Wei, Longbao; Manzoor, Faiza (Frontiers in Public Health, 2024)
This study focuses on the impact of education on health and health inequalities in rural areas of China. Education significantly enhances economic status and health, driving economic growth and improving public health standards. Integral to the “Healthy China Strategy,” it provides essential guidance for public policy and underscores the need for strategic human capital investments to achieve these goals. The study utilizes data from the China Family Panel Studies (CFPS) spanning 2010–2020 and employs the average educational level within counties as an instrumental variable. The causal impact of education on health and health inequalities is estimated using the two-stage least squares (2SLS) method. The findings reveal a significant positive correlation between enhancing education levels and health improvements. Specifically, after controlling for endogeneity, the duration of individual education significantly improves both subjective and objective health outcomes. It reduces health inequalities, with these effects being more pronounced among women and low-income groups. Mechanistically, education positively impacts health primarily by altering health behaviors and social network levels and reducing health inequalities through socio-economic factors. This paper provides important implications for public policy, suggesting that enhancing educational investments can drive economic development and improve population health standards.